Outcomes in Neonates Receiving Therapeutic Hypothermia and Extracorporeal Membrane Oxygenation versus Extracorporeal Membrane Oxygenation Alone - Cicalese, Erin; Seltzer, Bryn H.S.; Fisher, Jason C.; Verma, Sourabh (American Journal of Perinatology, 2024)
This study aimed to examine survival and outcomes in neonates who received therapeutic hypothermia (TH) for neonatal encephalopathy (NE) and extracorporeal membrane oxygenation (ECMO) versus ECMO alone.This is a retrospective review of Extracorporeal Life Support Organization (ELSO) Registry data from 2007 to 2017 for neonates undergoing ECMO and TH for NE (TH/ECMO) or ECMO alone. Primary outcomes were ECMO survival and survival to discharge. Secondary outcomes were complications while on ECMO. Statistical analysis was performed using Fisher's exact and Mann–Whitney U tests. Multivariate regression was performed to identify predictors of ECMO survival.Of 3,672 neonates, 215 (6%) received TH/ECMO, while 3,457 (94%) received ECMO alone. There was no significant difference in ECMO survival (92 vs. 92%, p = 0.70) or survival to discharge (87 vs. 85%, p = 0.43) between groups. TH/ECMO group had higher hemorrhagic (29 vs. 20%, p < 0.01), neurologic (24% vs. 12%, p < 0.01), and metabolic (28 vs. 15%, p < 0.01) complications. Multivariate regression identified higher gestational age, absence of inotropes during ECMO, and lack of neurologic, pulmonary, or hemorrhagic complications as independent predictors of ECMO survival.Neonates undergoing ECMO and TH for NE had survival rates comparable to those receiving ECMO alone. These findings suggest that ECMO can be considered for neonates with NE undergoing TH who meet the criteria for ECMO.
Keywords: ECMO; therapeutic hypothermia; HIE; neonatal encephalopathy